Proceedings of the Twenty-Sixth International Joint Conference on Artificial Intelligence 2017
DOI: 10.24963/ijcai.2017/507
|View full text |Cite
|
Sign up to set email alerts
|

Cake Cutting: Envy and Truth

Abstract: We study envy-free cake cutting with strategic agents, where each agent may manipulate his private information in order to receive a better allocation. We focus on piecewise constant utility functions and consider two scenarios: the general setting without any restriction on the allocations and the restricted setting where each agent has to receive a connected piece. We show that no deterministic truthful envy-free mechanism exists in the connected piece scenario, and the same impossibility result for the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
(16 reference statements)
0
38
0
Order By: Relevance
“…As with the connected piece assumption, Bei et al [2017] showed a similar negative result for position obliviousness with the free disposal assumption but using the larger class of piecewise constant valuations. For piecewise uniform valuations, Chen et al's mechanism is truthful, envy-free, and position oblivious under the free disposal assumption.…”
Section: Impossibility Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…As with the connected piece assumption, Bei et al [2017] showed a similar negative result for position obliviousness with the free disposal assumption but using the larger class of piecewise constant valuations. For piecewise uniform valuations, Chen et al's mechanism is truthful, envy-free, and position oblivious under the free disposal assumption.…”
Section: Impossibility Resultsmentioning
confidence: 69%
“…Since this holds for any y > x, if we take some z > y (obviously z > x also), we find that no allocation works when both agents report [0, z], a contradiction. Bei et al [2017] showed that a similar impossibility result holds even with the free disposal assumption, but using the larger class of piecewise constant valuations. For the class of valuations that we consider in Theorem 4, there exists a simple truthful and envy-free mechanism that always returns a connected allocation assuming free disposal.…”
Section: Impossibility Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This is the standard notion of strategy-proofness in mechanism design. For a weaker notion see[7,8] 4. Formally, for any ϵ ∈ [0, 1], the procedure p is ϵ -strategy-proof if for every agent i, every collection of valuations functions(v i , v −i ), and every other valuation function v ′ i , v i (p i (v i , v −i )) ≥ v i (p i (v ′ i , v −i )) − ϵ .…”
mentioning
confidence: 99%